The Augustan art of poetry Augustan translation of the classics - Sowerby, Robin (Oxford University Press, 2006)
Robin Sowerby uses translations to explore the artistic influence of the Roman poetry of the Augustan age upon English neoclassical poetry. He foregrounds the artistry of the central texts, such as Dryden's translation of Virgil and Pope's Homer.